A Formal Solution to Reichenbach's Reference Class Problem. (14th November 2019) - Thorn, Paul D.
Abstract: Following Reichenbach, it is widely held that in making a direct inference, one should base one's conclusion on a relevant frequency statement concerning the most specific reference class for which one is able to make a warranted and relatively precise‐valued frequency judgment. In cases where one has accurate and precise‐valued frequency information for two relevant reference classes, R1 and R2, and one lacks accurate and precise‐valued frequency information concerning their intersection, R1 ∩R2, it is widely held, following Reichenbach, that no inference may be drawn. In contradiction to Reichenbach and the common wisdom, I argue for the view that it is often possible to draw a reasonable informative conclusion in such circumstances. As a basis for drawing such a conclusion, I show that one is generally in a position to formulate a reasonable direct inference for a reference class that is more specific than either of R1 and R2 .